2023
DOI: 10.1161/strokeaha.123.042656
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Reactivity in Patients With Small Vessel Disease: A Cross-Sectional Study

Emilie Sleight,
Michael S. Stringer,
Una Clancy
et al.

Abstract: BACKGROUND: Cerebrovascular reactivity (CVR) is inversely related to white matter hyperintensity severity, a marker of cerebral small vessel disease (SVD). Less is known about the relationship between CVR and other SVD imaging features or cognition. We aimed to investigate these cross-sectional relationships. METHODS: Between 2018 and 2021 in Edinburgh, we recruited patients presenting with lacunar or cortical ischemic stroke, whom we characterized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…CO 2 -induced vasodilation is assessed by measuring cerebral blood flow (CBF) increases in response to breathing CO 2 with functional MRI using blood O 2 level–dependent (BOLD) response or arterial spin labeling, which can directly measure CBF. Two recent, large cross-sectional cohort studies showed that a reduced CO 2 response in the WM or subcortical gray matter is associated with more severe cSVD burden (WMHs, lacunes, microbleeds, enlarged PVSs, and brain atrophy) and impaired cognition ( 78 , 79 ). In a 1-year longitudinal study performed in patients with age-related WMHs, regions of normal-appearing WM that progress to WMHs over time had a lower baseline response to hypercapnia compared with normal-appearing WM ( 80 ).…”
Section: Vascular Mechanicsmentioning
confidence: 99%
“…CO 2 -induced vasodilation is assessed by measuring cerebral blood flow (CBF) increases in response to breathing CO 2 with functional MRI using blood O 2 level–dependent (BOLD) response or arterial spin labeling, which can directly measure CBF. Two recent, large cross-sectional cohort studies showed that a reduced CO 2 response in the WM or subcortical gray matter is associated with more severe cSVD burden (WMHs, lacunes, microbleeds, enlarged PVSs, and brain atrophy) and impaired cognition ( 78 , 79 ). In a 1-year longitudinal study performed in patients with age-related WMHs, regions of normal-appearing WM that progress to WMHs over time had a lower baseline response to hypercapnia compared with normal-appearing WM ( 80 ).…”
Section: Vascular Mechanicsmentioning
confidence: 99%
“…The vascular dysfunction associated with cSVD has emerged as a promising biomarker of forthcoming cognitive decline. Apart from cerebral hypoperfusion, 6 there are important deficits in dynamic vascular function, namely neurovascular coupling (NVC) 7 and cerebrovascular reactivity (CVR), 8 mainly due to increased arterial stiffness and endothelial dysfunction. 9 In fact, it is the deficit in dynamic function of the vasculature, rather than in cerebral perfusion at resting state, which best predicts clinical outcomes, 10 including poor cognitive performance.…”
mentioning
confidence: 99%